Use of mediation to resolve the dispute over low-head hydroelectric development at Swan Lake - O'Connor, D. (New England Environmental Mediation Project, Boston, MA (USA), 1980)
In 1978, the Maine Hydroelectric Development Corporation announced that the company planned to renovate five dams on the Goose River near Belfast, Maine to generate electricity. The most important part of the plan involved the use of the first of the dams, at the lower end of Swan Lake, to regulate the flow of water to the downstream dams. For Maine Hydro, management of the Swan Lake dam could make an otherwise marginal proposal lucrative. However, Swan Lake is vitally important to the residents of Swanville. The town was so concerned about the impact of this proposed hydroelectric project that it petitioned the Federal Energy Regulatory Commission (FERC) to deny Maine Hydro's application on the grounds that it would damage the environment, reduce property values and eliminate recreational opportunities for its citizens. This report was written by the mediator of the dispute and represents the views and behavior of the parties as the mediator understood them. It is intended to present the mediator's observations in a way which will inform and assist others who may someday face a difficult situation like the one the Town of Swanville and Maine Hydroelectric Development Corporation faced, and successfully resolved, in the spring and summer of 1979.